2018
DOI: 10.1016/j.ces.2018.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on methanol adsorption on functionalized graphite: Saturation of functional groups

Abstract: Grand Canonical Monte Carlo simulation of methanol adsorption on a graphite model with two hydroxyl groups grafted on the surface has been carried out to investigate the effects of temperature in the range of 278-360K. The spacing between the OH groups was chosen so that two hydrogen bonds could be formed with the first methanol molecule. In the Henry law region, the isosteric heat at zero loading is greater than the condensation heat. When the loading is increased, the isosteric heat at low temperatures decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…We modeled graphite as a homogeneous substrate with a constant surface density of 38.2 nm –2 , and the potential energy between an LJ site and graphite was modeled with the Steele 10-4-3 potential equation, with the molecular parameters for the carbon atom in a graphene layer taken from Steele, σ i (s) = 0.34 nm and ε i (s) / k B = 28 K. The interlayer distance between the two graphene layers was 0.3354 nm. The homogeneous solid model was used since it was used in previous studies and gave consistent results with experimental data for a wide variety of fluids, including ethanol and methanol. …”
Section: Theory and Methodsmentioning
confidence: 90%
“…We modeled graphite as a homogeneous substrate with a constant surface density of 38.2 nm –2 , and the potential energy between an LJ site and graphite was modeled with the Steele 10-4-3 potential equation, with the molecular parameters for the carbon atom in a graphene layer taken from Steele, σ i (s) = 0.34 nm and ε i (s) / k B = 28 K. The interlayer distance between the two graphene layers was 0.3354 nm. The homogeneous solid model was used since it was used in previous studies and gave consistent results with experimental data for a wide variety of fluids, including ethanol and methanol. …”
Section: Theory and Methodsmentioning
confidence: 90%
“…Volatile organic compounds (VOCs) are harmful to the human body and the environment. These chemicals come from a vast range of sources, such as exhaust emissions, painting, textile printing, petrochemical, coal chemical industry, etc. VOCs are of various types and can be categorized into polar and nonpolar VOCs according to the degree of polarity of molecules. Up to date, many different technologies have been proposed to eliminate VOC emissions, including adsorption, , condensation, catalytic oxidation, biodegradation, and other recovery and removal methods. In these processes, adsorption–desorption has been considered the most efficient method of removing and recovering organic pollutants .…”
Section: Introductionmentioning
confidence: 99%
“…In cooperation with experiments, computer simulation has been widely used and plays an important role in revealing both macroscopic and microscopic behavior as well as details of the adsorption on a atomistic level and can serve as a large-scale prescreening tool. , The grand canonical Monte Carlo (GCMC) simulation technique is commonly used in studying gas adsorption. Several GCMC studies of total isosteric heat for CO 2 adsorption in IRMOF-1 have been reported in the literature, and a few papers have appeared which distinguish the fluid–fluid (F–F) and fluid–solid (F–S) interactions for CO 2 adsorption on other MOFs. , It has been noted that the isosteric heat of adsorption at low loadings (in the Henry Law region) can be attributed to the interaction energy between an adsorbate molecule and the most favorable binding sites in the adsorbent. Although the heat data are essential in the design of adsorbent materials, to the best of our knowledge, the separate heat contributions between CO 2 or other adsorbates and each atom type in IRMOF-1 and other MOFs have not been explored.…”
Section: Introductionmentioning
confidence: 99%